Nursing telemonitoring in chronic patient management - Thais Mota Loiola; Mourão, Carla (Revista da UI_IPSantarém, 2024)
Objective: This study aims to evaluate the evidence available in the literature on the impact of telemonitoring in monitoring patients with chronic diseases. Methods: This was an integrative literature review study. The articles were collected between the months of July/2023 and October/2023, in the VHL – Virtual Health Library database, following the inclusion and exclusion criteria. After applying the criteria, 14 articles were selected to read the titles and abstracts; 10 articles to read in full, six of which were included in the review to collect the results. Results: In the final sample, the articles were divided into three themes: telehealth as a clinical protocol for decompensated diabetics, use of mobile telephony as a tool for self-management of chronic conditions, and cost-effectiveness of digital health. Final Considerations: telemonitoring in the management of chronic patients has positively impacted the clinical results and well-being of these patients, providing autonomy and self-management of their own disease, as well as the financial resources of health services, generating savings and profitability.